Changes of GABA receptor and immunoreactivity modification of IP3 & BDNF-TrkB in KA-induced rat epileptogenic hippocampal neuronal culture - Nei, Chong Pei (2018)
INTRODUCTION: Epilepsy seizure is a common condition occurring in approximately 50 million people worldwide. Epilepsy seizure is a transient occurrence of sign and or symptoms due to abnormal excessive or hypersynchronous activity in the brain. Studies showed GABAAR supporting the role of BDNF-TrkB as a neuroprotective factor in the hippocampus and BDNF-TrkB triggers one of the downstream signalling IP3R which is involved in epilepsy seizure. However, past studies focus on in vivo and in vitro organotypic hippocampal slices culture. It is unclear whether the findings of the current study would extrapolate in vitro dissociated primary rat hippocampal neuron culture. OBJECTIVE: To study the changes of γ-Amino butyric acid A receptor (GABAAR), Brain derived neurotrophic factor (BDNF), Tyrosine kinase receptor B (TrkB) and Inositol 1, 4, 5 triphosphate receptor (IP3R) in normal and epileptogenic hippocampal neuron.METHOD: In this study, chemo-convulsant method, kainic acid (KA) induced seizure applied to (E-18) rat hippocampus neuron. The E-18 rat hippocampus neuronwas cultured based on the optimised method by using poly-L-lysine coated glass coverslips (Todd et al., 2013). The day in vitro (DIV), 14 culture neurons induced with 0.5μMKA for 30 (KA30), 60 (KA60) and 90 (KA)minutes respectively. The normal and KA treated neuron underwent cell viability, neurite outgrowth density assessment and immunocytochemistry assessment respectively. RESULTS: Finding showed no significant effects of GABAA α1-containing receptors (GABAA α1 containing R )and BDNF of the KA treatment to the normal neuron culture. The TrkB receptor was significantly decreased by the treatment (F (3, 8) = 8.761, p < 0.01). The KA30, KA60 and KA 90 were significant decreased compared to the control group with no KA treated culture. The IP3R was elevated significantly y the treatment of KA (F (3, 8) = 6.954, p < 0.05) . CONCLUSIONS: The KA administration on hippocampal neuron culture showed an increase expression in the TrkB (BDNF receptor) and IP3R significantly whereas, the immunoreactivity of BDNF and GABAA α1 containing R showed a decreased expression that is not statistically significant. Altogether, our study showed that KA administration on in vitro rat hippocampal neuron induces epileptogenesis which, results in changes in the GABAA α1 containing R, BDNF, TrkB and IP3R.